The Depiction of Tolerance in American Superhero Films - Stanley, Jeremy; Setyadi, Yuan; Rudy, Rudy (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
It is true that film as medium can represent a lot significant values in society, one of them is tolerance. It is crucial to discuss tolerance because societies have become more diverse. Therefore, exploring tolerance on films can be fascinating and useful. By using American superhero films (Fantastic 4 (2005), Fantastic 4: Rise of the Silver Surfer (2007), and Black Panther (2018) to depict how tolerance is represented, this study offers to enhance the understanding of tolerance which has always been one of important values to have. By applying Hall’s theory of representation, this study exposes two essential points: tolerance must be conceptualized by incorporating mutualism, understanding, and peace; and tolerance shown on American superhero movies should incorporate the portrayal of race and gender.